The Effect of Government Expenditure and Interest Rates on Inflation in Asia - Maharani, Henni Oktavia; Yuliawan, Dedy; Sitorus, Nurbetty Herlina (Cita konsultindo, 2025)
This study examines the impact of government expenditure and interest rates on inflation in Asia from 2018 to 2023. Using panel data from 31 Asian countries, the research employs quantitative methods with descriptive analysis. The study finds that government expenditure has a statistically significant negative effect on inflation, meaning that higher government spending reduces inflation, while reduced spending increases it, mainly due to fiscal deficits. On the other hand, interest rates have a positive effect on inflation, with higher interest rates leading to increased inflation, largely influenced by the post-COVID-19 economic recovery and the Russia-Ukraine conflict. Additionally, the study shows that both government expenditure and interest rates jointly influence inflation, with a confidence level of 95%. The results highlight the importance of effective fiscal policy and clear communication from central banks regarding interest rate adjustments. The study recommends that governments prioritize efficient spending, while central banks should enhance transparency in their monetary policy decisions. The paper also suggests that future research should expand the analysis period and sample size to gain deeper insights into the relationship between fiscal and monetary policies and inflation in Asia.